Laju Perpindahan Panas Pada Karbon bambu Betung Dengan Variasi Temperatur Karbonisasi 500oC, 600oC, 700oC, dan 800oC - Wardana, Alex; Wijaksana, Hendra; Astawa, I Ketut (Teknik Desain Mekanika; Vol 10 No 3 (2021): Juli 2021 : Teknik Desain Mekanika, 2021)
Abstractt This study aims to determine the characteristics of the heat transfer rate of bamboo betung as a pad material in a direct epaporative cooling system. Betung bamboo will be carbonized with temperature variations of 500 oC, 600 oC, 700 oC, 800 oC with a heating reactor temperature of 100 oC/hour. From the test results, the highest heat transfer rate value was found in the bamboo betung specimen with a temperature of 600 C at 21.55 x 10-5 watts and the lowest heat transfer rate value at 700 oC specimen at 7.16 x 10-5 watts. Bamboo betung specimens with a temperature of 600 C have the potential to be pad materials for direct evaporative cooling systems. Keywords: Direct Evaporative Cooling, Betung Bamboo, Carbonization, Heat Transfer Rate